Evaluation Of The Oil Potential, Kerogen Type And Degree Of Maturation Of The Kipala Shales (Kwilu Province,Democratic Republic of Congo) Based On Rock-Eval Parameters - Munene Asidi, Djonive; Mayena, Thomas Kanika; Mwanza, Fredéric Makoka; Levesque, Makuku Mbo; Adalbert Jules, Makutu Ma Ngwayaya; Ruben, Koy Kasongo (UIR PRESS, 2026)
This note aims to contribute to the assessment (still rudimentary at this stage) of the oil potential, kerogen type and degree of maturation of the Kipala shales, using Rock Eval parameters (TOC or COT: Total Organic Carbon; Tmax: Maximum Temperature; Peaks S1, S2, S3; IO: Oxygen Index; HI: Hydrogen Index; PI: Production Index; PP: Production Potential; RC: Residual Carbon; MINC: Mineral Carbon), as well as the associated geochemical diagrams, based on ten samples of these shales analysed by Rock Eval Pyrolysis at the PETROCCI laboratory in Côte d'Ivoire. The main results of this assessment can be summarised as follows: (i) based on the criteria established by Espitalié et al. (1977), the high TOC content (6 to 15%) of these Kipala rocks classifies them as excellent hydrocarbon source rocks; (ii) the kerogen in the shales studied is ‘Type I’; (iii) the evolution of their organic matter is at the ‘Immature-Mature’ limit; with the exception of two samples which, with their relatively high Tmax (435°C < Tmax > 455°C), are classified as mature rocks; i.e. rocks that have reached ‘oil window’ conditions; (iv) almost all of the Kipala shales are classified as source rocks producing good quality oil; (v) the very high PP values of these shales classify them as rocks with very good to excellent potential, suggesting that they can generate hydrocarbons; (vi) IP values < 0.1 for most of the shale samples analysed, coupled with their low Tmax values (< 435°C), suggest that the organic matter in these shales is “immature” or even “early mature”, as evidenced by the presence of traces of bitumen in some of the shale samples.